PENERAPAN STANDAR GIZI MAKANAN BAGI NARAPIDANA BERDASARKAN PERMENKUMHAM NOMOR 40 TAHUN 2017 DI LAPAS PEREMPUAN KELAS IIA JAKARTA - Bening Kumalasari, Ayu; Sulisrudatin, Nunuk (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
This study aims to determine the implementation of nutritional standards in the provision of food in the kitchen of Class IIA Jakarta Women's Prison for inmates. Based on the results of the research conducted by the author, the author can conclude that the Class IIA Jakarta Women's Prison Kitchen has attempted to maximize the implementation of nutritional standards in the process of food provision activities referring to Permenkumham no. 40 of 2017. Factors that are obstacles in the provision of food at Class IIA Jakarta Women's Prison, Include: a. The number of food service personnel is still not fulfilled, causing overlapping in work, b. daily food quality is not directly monitored by the nutrition team and there are no food recommendations if there are sick prisoners, c. there are several infrastructures that must be met to maximize food services for prisoners in the Class IIA Jakarta Women's Prison. The research method used is Juridical Empirical. Juridical is to study the normative concept or legislation. This study analyzes the Implementation of nutritional standards in the Minister of Law and Human Rights Regulation No. 40 of 2017 in the Class IIA Jakarta Women's Prison. The results of the study indicate that the Class IIA Jakarta Women's Prison has attempted to provide the rights of prisoners in the form of getting decent food services according to nutritional needs which are the rights of prisoners in the Prison.